Romanian Public Servants on Public Administration Reforms - Sorin Dan ȘANDOR; Ciprian TRIPON (Transylvanian Review of Administrative Sciences, 2008)
The present paper tries to assess the public administration reforms based on the opinions of public servants – the ones in charge with the actual implementation of the reforms. In November 2007 a mail survey was done in Romanian PA institutions. The opinions showed the necessity of the administrative reforms is accepted mainly as a request of the European Union. The way in which reforms were done is seen as a strenuous process, characterized by low coherence, with many changes of focus and done mainly through enacting new legislation over and over, which led to over-regulation. De-centralization (financial and managerial) has still a long way to go, legislative improvement also (especially streamlining rules and procedures), citizens/community is not seen as a real partnership. More optimistic answers are regarding the functioning of local institutions (especially along the organizational culture dimension), which are seen as functioning very well in the context of reforms (a cautionary note should be made – loyalty or subjectivity may have lead to such answers).